Hubungan Tingkat Pengetahuan Tentang Perawatan Intensive Care Unit (ICU) Dengan Kecemasan Keluarga Pasien Yang Di Rawat Di ICU RS Kanker Dharmais - Yuli Irawati; Zahrah Maulidia Septimar; Inna Mukhaira (Pusat Riset dan Inovasi Nasional, 2024)
Background: The description of patients in the ICU is a description of critical patients and has different vulnerabilities. Patients who are treated in critical care units can pose a threat to the life and well-being of patients, and are considered as a sign of imminent death, this condition causes anxiety. in patients and families. Objective: To determine the relationship between the level of knowledge about Intensive Care Unit (ICU) care and the anxiety of the families of patients treated in the ICU of Dharmais Cancer Hospital. Methods: This study uses a quantitative descriptive cross-sectional approach. A sample of 51 family respondents who are being treated at the ICU of Dharmais Cancer Hospital in Desember 2022 up to January 2023. Data was obtained using a questionnaire. The analysis used is Chi Square. Results: The frequency distribution of the level of knowledge about Intensive Care Unit (ICU) care is mostly good (75.2%) and moderate family anxiety (82.2%). There is a relationship between the level of knowledge about Intensive Care Unit (ICU) care and the anxiety level of the families of patients who are treated in the ICU at Dharmais Cancer Hospital with the Chi Square correlation test, it is known that the significance is p = 0.001 (α: <0.05). Conclusion: There is a relationship between the level of knowledge about Intensive Care Unit (ICU) care and the anxiety level of the patient's family who is treated in the ICU of Dharmais Cancer Hospital